G. K. Chesterton’s rhetoric in defense of the family: an analysis of the articles published in The Illustrated London News (1905–1936) - Alla Kovalenko (Church, Communication and Culture, 2019)
This is an in-depth analysis of the style and rhetoric read in G. K. Chesterton’s essays on the topic of marriage, divorce and the institution of the family, written for The Illustrated London News during the years 1905–1936. A journalist and writer, Chesterton introduced a persuasive defense of common sense during a time when our present-day cultural and social context was still in its formative phase. This, in conjunction with the uniqueness of his style and the structure of his argumentation, which integrates well with different forms of communication, render his rhetoric and ideas on defense of the family altogether relevant, topical and exemplary.